Study of intraoperative squash cytology of intracranial and spinal cord tumors - Bhardwaj, Karn; Kriplani, Dipsha; Bhake, Arvind; Bhardwaj, Kavita (International Journal of Research in Medical Sciences, 2017)
Background: The aim was to study the cytomorphology of neoplastic lesions of brain and spinal cord by intraoperative squash cytology, compare it with the histopathological diagnosis on excision biopsy/surgical specimen and establish a correlation. The causes of erroneous diagnoses achieved at squash cytology of intracranial and spinal cord tumors were ascertained. Tumor types having the advantage of diagnostic certainty by squash cytology of intracranial and spinal cord lesions was also determined. Methods: Squash preparations of 70 patients suspected to have neoplasia were made and stained with rapid hematoxylin and eosin stain and rapid Papanicolaou stain. A few squash smears were also dry fixed and stained with Giemsa stain. The smears were typed according to the cytomorphological criteria and the cytodiagnoses was compared with the histopathological diagnoses and a correlation was established. Results: A positive predictive value for intraoperative squash cytology for diagnosis of intracranial and spinal cord tumors was seen to be 100% and a negative predictive value of 97.22% were established by this study. The sensitivity was found to be 97.22% and the specificity was 100%. Thus, the accuracy of the study was 98.57%. Conclusions: Squash smear cytology of the brain and spinal cord tumors performed intraoperatively for diagnostic consultation fulfills all the determinants of an excellent diagnostic modality.